Relationship between exposure, preferred genre and pacing of television program with primary school students' aggressive behavior in Iran - Nazari, Mohammad Reza (2013)
Children are among the population most at risk for experiencing violence. Children also spend a great deal of their free time engaged in media consumption, much of which includes increasingly violent content. Media violence has been a topic of both public and scientific concern for over 50 years. There are literally hundreds of studies that provide evidence that exposure to television violence leads to subsequent physical aggression in viewers. However, the effects of television violence would depend on the type of content viewed and the pace of programs viewed. In the past few decades, a subset of research has focused on how the structural features of media alter viewers' cognitive and emotional processes. Research has shown that how message sensation value influences emotional responses and how the speed of pacing in some children's programs has detrimental effects on their aggressive behavior; therefore, pacing has been most actively investigated in related literature. In this study, pacing is measured based on six essential criteria as suggested by the literature. In relation to this study, relatively little attention has been paid to television program pacing on aggressive behavior among elementary students in Iran. The purpose of this study is to examine the relationship between television program pacing and aggressive behavior in primary school students. Two phases were conducted in this study to comprehensively explore this phenomenon. The first phase consisted of a survey with 424 primary school students (aged 7-12 years) in the five provinces of Iran which were selected through a multi-stage random sampling from different geographical areas comprising of North, South, West, East and Central area of Iran. This survey investigated whether exposure to television program was related to children's use of media that explored using Buss - Perry standard questionnaire. The results of the survey revealed a significant relationship between amount of exposure to television program and aggressive behaviors among primary school students (p<0.05). In addition, the students' aggression was positively associated with watching movies with action adventure genre (p<0.05). According to the findings obtained from the first phase of the study, a total of 22 programs were selected as the most favorite children's TV programs which were assigned to a technical content analysis known ,as pacing. The second phase of the present study included a pacing index derived from the following criteria: (a) frequency of camera cuts, (b) frequency of related scene changes, (c) frequency of unrelated scene changes, (d) frequency of auditory changes, (e) percentage of active motion, (f) percentage of active talking, and (g) percentage of active music. The findings of the study showed that the highest pacing index was attributed to Pokemon (67.08), while Fetileh ranked as the lowest pacing index program (23.86). The results also revealed that TV program pacing scores were significantly and positively associated with aggression level of primary school children (p<0.05). The results of this study suggested the need for further attention on children's television program production to protect them from antisocial behaviors and interventions for violence-exposed children in order to reduce negative outcomes. Finally, more research is needed to focus on the relationships of pacing with dependent measures, such as violent behaviors, learning process, social interaction, and problem solving.